(untitled) (Tanzania Journal for Population studies and Development, 2022)
This study explored employers’ perception towards child domestic workers in Dar es Salaam, Tanzania. It involved a sample of 15 employers of child domestic workers. Data was gathered through key informant interviews and field observation, and analysed thematically between August 2021 and February, 2022. The findings indicate that child domestic workers (15–18 years old) are culturally acceptable in the name of work socialization, are often perceived and treated as fictive kin, and are a key ingredient in employers’ households. However, some employers had negative perception towards child domestic workers and described them as stubborn, witchy, and lazy; hence kept on hiring and firing these child domestic workers from time and space. It is therefore concluded that in the context of developing and mid-income countries like Tanzania where most people, including the elite, consider child domestic work as a charity, socially and culturally removing children from domestic work is not enough; and may leave them more vulnerable to other dangerous forms of work within or outside their biological homes. Hence, the study recommends that the human rights of children—like their right to light work, their best interests, and their voices and those of their employers—remain to be vital aspects of policies affecting children. Again, in line with the current International Labour Organization’s emphasis on making domestic work decent, there is a need of implementing strategies to promote positive work experiences among child domestic workers (15–18 years old), and formalize/regulate their employment across Tanzania.